Art: The Spiritual Path to God - Sulaiman (Jurnal Theologia, 2021)
Art has long been a means of expression that serves to create aesthetic works and as a spiritual path that connects the individual to the transcendental dimension and God. In Islam, art has a vital role as a medium for achieving closeness to God, where works such as calligraphy, geometric art, and mosque architecture serve as decoration and meditative and reflective means. The background of this research is the increasingly strong influence of materialism and commercialization in modern art, which has led to the loss of spiritual dimension in artworks. This article uses literature study methodologies and case studies to explore how art remains relevant as a spiritual path in traditional and modern contexts. In the literature study, the author examines works that discuss the relationship between art and spirituality in the Islamic tradition and the contribution of Islamic art in strengthening awareness of God. The results of this study show that although the modern art world is often focused on the commercial aspect, art still has excellent potential to be a spiritual means that can connect individuals with God, personally and collectively. Contemporary Islamic art, through digital technology and interactive media, has managed to create an immersive and immersive spiritual experience for its connoisseurs.